A fuzzy multi-objective multi-period network DEA model for efficiency measurement in oil refineries. (September 2019) - Tavana, Madjid; Khalili-Damghani, Kaveh; Santos Arteaga, Francisco J.; Hosseini, Amineh
Highlights: We define a fuzzy multi-objective multi-period network Data Envelopment Analysis model. The model is applied to evaluate the dynamic efficiency of several Iranian oil refineries. Their enhancement of the environmental scope of the production process is also measured. The performance of oil refineries is evaluated in the presence of undesirable outputs. A real-life case study illustrates the efficacy and applicability of the proposed method. Abstract: We define a fuzzy multi-objective multi-period network DEA model customized to evaluate the dynamic performance of oil refineries in the presence of undesirable outputs. In particular, we use a standard fuzzy operator to define the efficiency levels so as to integrate multiple objectives and periods of time within a unique maximization framework. Managers and decision makers are provided with a model characterized by its operational simplicity that allows for the straightforward implementation of standard spreadsheet software. The model is applied to a real-life case study, where the capacity of refineries to optimize their performance through the refining process is analyzed together with the introduction of value-added products that preserve and enhance the environmental dimensions of the refining process. The inclusion of a real-life case study aims at illustrating the efficacy and applicability of the proposed method relative to those of more conventional models. Moreover, the range of the time period covered allows us to analyze the evolution of efficiency beyond the standard two-period Malmquist framework generally considered in the literature dealing with the behavior of refineries.